Perbandingan Pengampuan Negara Indonesia dengan Negara Singapura - Aqil Tajuddin Zhahir; Danar Aji Kirana; Alfiyan Rahmat dani Utomo; Wisnu Hesa (Universitas Wahid Hasyim, 2024)
This article examines the differences in guardianship, or curatele, between Indonesia and Singapore. The objective is to identify the types and distinctions of guardianship in these two countries. The research is descriptive in nature, with legal materials collected through a literature study using primary and secondary sources. The findings reveal that there are indeed differences between Indonesia and Singapore. In Indonesia, an individual under guardianship is referred to as a Kurandus, which includes those who are mute, mentally ill, or have impaired vision. The Guardian, or curator, typically has rights and duties as determined by the Court at the time of their appointment. In contrast, in Singapore, a person under guardianship is known as a donor, and this is not limited to individuals who are mentally incapacitated; even those who are mentally sound can become donors. Additionally, there are two types of Guardians in Singapore: Donees and Deputies, both of whom have the right and obligation to make decisions on behalf of the donor.Â